2017
DOI: 10.21580/pjpp.v2i1.1357
|View full text |Cite
|
Sign up to set email alerts
|

Bahagia dalam Meraih Cita-cita: Kesejahteraan Subjektif Mahasiswa Teknik Arsitektur Ditinjau dari Regulasi Emosi dan Efikasi Diri

Abstract: <p class="IABSTRAK"><strong>Abstract: </strong>Subjective well-being is people’s evaluation of they life. It includes evaluation about cognitive and affective. People have higher subjective well-being, they have a more positive affective or good feelings and satisfied with the life they have. Contrary, people who have lower subjective well-being tend to overcome negative feelings in him. Therefore, subjective well-being is very important in the life of every individual is no exception to the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
4
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 6 publications
1
4
0
Order By: Relevance
“…The strength of this role can be seen from the value of t = 11.875 with a significance level of p = .00, p < .05. This is in line with Alfinuha and Nuqul (2017) research, which demonstrates that self-efficacy can affect subjective well-being. Students with high academic self-efficacy will consider that the school assignments they are given, both difficult and easy, are part of the learning process (Saraswati & Ratnaningsih, 2017).…”
Section: Discussionsupporting
confidence: 91%
“…The strength of this role can be seen from the value of t = 11.875 with a significance level of p = .00, p < .05. This is in line with Alfinuha and Nuqul (2017) research, which demonstrates that self-efficacy can affect subjective well-being. Students with high academic self-efficacy will consider that the school assignments they are given, both difficult and easy, are part of the learning process (Saraswati & Ratnaningsih, 2017).…”
Section: Discussionsupporting
confidence: 91%
“…The direct effect of self-efficacy on subjective well-being is in line with the results of previous studies. Santos et al (2014), Alfinuha and Nuqul (2017), Salehi et al (2016), and Tamannaeifar and Motaghedifard (2014) showed that self-efficacy affects subjective wellbeing. Self-efficacy helps regulate negative emotions, which is an important factor in subjective well-being (Cattelino et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…Research by Mudzkiyyah (2022) also revealed that peer attachment and academic self-efficacy significantly influence well-being. Many studies have confirmed a positive correlation between self-efficacy and subjective well-being (Agustin & Afriyeni, 2016;Alfinuha & Nuqul, 2017;Santos et al, 2014). A meta-analysis also revealed that self-efficacy is positively correlated with resilience (Utami, 2017).…”
Section: Introductionmentioning
confidence: 93%
“…Furthermore, research by Situmorang, Wibowo, & Mulawarman (2018) concluded that CBT is effective in increasing students' self-efficacy. Selfefficacy and emotion regulation emphasizes the existence of happiness in students (Alfinuha & Nuqul, 2017). Therefore, it is expected that the cognitive behavioral therapy approach can improve the quality of life and self-efficacy in patients with rheumatoid arthritis.…”
Section: │ 203mentioning
confidence: 99%